Effects of treatment with sitagliptin on hepatotoxicity induced by acetaminophen in mice - Wafaa Ahmed Hewedy (Universidade de São Paulo, 2021)
Up to date, the management of hepatotoxicity induced by a suicidal or unintentional overdose of acetaminophen (APAP) remains a therapeutic challenge. The present study aimed to elucidate the potential effect of sitagliptin, a DPP-4 inhibitor, to ameliorate the acute injurious effects of acetaminophen on the liver. APAP toxicity was induced in mice by an intraperitoneal injection of APAP (400 mg/kg). The effect of treatment with sitagliptin, initiated 5 days prior to APAP injection, was evaluated. Serum indices of hepatotoxicity, oxidative stress markers in liver tissues, serum IL-1β, and TNF-α in addition to hepatic- NF-E2-related factor-2 (Nrf2) were determined. Our results showed that APAP induced marked hepatic injury as evidenced by an increase in serum levels of ALT and AST, in addition to the deterioration of histological grading. Oxidative stress markers, serum TNF-α, and IL-1β were also elevated. Sitagliptin successfully ameliorated the histological changes induced by APAP, improving liver function tests and liver oxidant status accompanied with a marked increase in Nrf2 level in hepatic tissues. Thus, the hepatoprotective effects of sitagliptin in this animal model seem to involve Nrf2 modulation, coincidental with its anti-inflammatory and antioxidant effects.